DATA ANALYSIS OF COMMERCIAL AIRCRAFT LANDING ON THE RUNWAY AIRPORTS IN INDONESIA - Rossi PASSARELLA; Siti NURMAINI; Muhammad Naufal RACHMATULLAH; Osvari ARSALAN; Rizki KURNIATI; Aditya ADITYA; Indra Gifari AFRIANSYAH; Rifqi FATHAN; Rani Silvani YOUSNAIDI; Harumi VENY (Scientific Journal of Silesian University of Technology. Series Transport)
A runway excursion is a runway safety issue in which an aircraft exits the runway improperly. Therefore, we believe it is necessary to conduct a data investigation of commercial airplanes landing at the airport in order to provide criticism, learning, and social control to airlines and air service policymakers in Indonesia so that they can become involved in protecting public transportation users, particularly those using air transportation. This study focuses on the procedural safety of commercial airplanes landing on the runway at airports in Indonesia. The data utilized for landing analysis is historical ADS-B data collected and acquired from the Flightradar24 website in 2019. The approach utilized in this study is exploratory data analysis (EDA), in which we explored the dataset to find trusted data (128 tier-1 data points). The results of this study showed that the aircraft that was the object of research was unlikely to land at the Touch Down Zone (TDZ), while the rest showed that its landing was highly likely outside the TDZ.